Fermented foods production using isolated Lactobacillaceae species for the improvement of vaginal health: the case of mageu and yoghurt - Hartzenberg-Aeroe, Ellen (Department of Chemical Engineering, 2023)
Bacterial vaginosis (BV) is the most prevalent vaginal dysbiosis affecting women's reproductive health. The condition is characterised by the disruption of a Lactobacillus spp.-dominated microbiota that is associated with positive health outcomes and a shift to a microbial community that consists of diverse obligately anaerobic bacteria. Currently, antibiotics are used to treat BV and other vaginal infections. However, post-therapy recurrence and reinfection rates are high, suggesting the need for adjunctive therapy. Probiotic supplements can be used in conjunction with antibiotic treatment to re-establish the optimal vaginal microbial community. Of the probiotic products available in South Africa, only a limited number are specifically for vaginal health and none contain probiotic microorganisms found in the female genital tract. Additionally, the healthy vaginal microbiota differ with geography. Therefore, there is a need for an affordable probiotic product targeted for South African women. In this dissertation, mageu and yoghurt are investigated for their potential as probiotic delivery vehicles. Previously isolated Lactobacillaceae strains from the genital tracts of healthy South African women are tested for their ability to ferment maize meal to mageu and milk to yoghurt, both as pure cultures and supplemented with traditionally-used microorganisms: Saccharomyces cerevisiae for mageu and Streptococcus thermophilus for yoghurt. Protocols were developed for the production of mageu and yoghurt with the bacterial strains. During production, fermentation was monitored by measuring pH until the end points of 3.5 and 4.5 were reached for mageu and yoghurt, respectively. After fermentation, the products were analysed by measuring titratable acidity, lactic acid and ethanol concentrations, total solids content, viable cell counts, qualitative analysis and shelf-life. Four mageu samples were then analysed for their consumer acceptability by an untrained consumer panel. The Lactobacillaceae isolates, both as pure strains and supplemented with S. cerevisiae, were able to ferment maize meal to mageu, producing a product with a final pH of around 3.5, which qualitatively resembled mageu. The presence of pH-lowering metabolites including lactic acid and other acids was also measured using titratable acidity. The addition of S. cerevisiae significantly reduced the fermentation time and increased the titratable acidity of all mixed culture samples compared to the pure culture mageu samples. All mageu samples produced using the Lactobacillaceae isolates met the ethanol (maximum 2.5 g/L) and total solids content (minimum 8% (m/m)) production requirements set by the South African National Standards. After one week at room temperature or refrigerated, none of the mageu samples had pH values below 3, which is acceptable for mageu. However, the mixed culture mageu samples saw a larger drop in pH over the week than the pure culture samples. The sensory analysis investigated the consumer acceptability of four probiotic mageu samples, a positive control produced with flour as the inoculum source, and a commercial sample. The commercial sample was generally preferred, and was scored highest by the consumer panel, while the other samples received mixed results. The spread of results was attributed to the influence of individual preference due to the small cohort size. The pure Lactobacillaceae strains were unable to ferment milk to yoghurt. By hour 12, the pH values were still between 6.32 and 6.37, and curdling of the product had occurred by hour 24. However, when supplemented with S. thermophilus, the mixed cultures were able to produce a product with a final pH of around 4.5 that qualitatively resembled traditional yoghurt. However, it is not known if the improved fermentation was due to S. thermophilus activity alone. The titratable acidity results also confirmed that pH-lowering metabolites were produced and all yoghurt samples had titratable acidity values greater than 0.6% (m/m), the minimum requirement for yoghurt. Little difference was observed between the samples for the qualitative assessment; however, the positive control had a thicker consistency than the probiotic samples. These results show that the Lactobacillaceae isolates when supplemented with traditional fermentation microorganisms are able to produce mageu and yoghurt. During this project protocols for mageu and yoghurt production using the Lactobacillaceae isolates specific to South African women were designed. This project serves as the first step towards investigating the use of fermented foods as affordable probiotic delivery vehicles for the improvement of vaginal health in South African women.